A Non-Blind Image Watermarking Method for Copyright Protection (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this paper, a non-blind watermarking method for protecting the copyright of digital color images is introduced. This method based on the combination of digital transforms (DWT, DCT) in the frequency domain. The embedding process in this method depends on the partition of the host image into 16×16 non-overlapped blocks and the use of edge entropy metric to choose the appropriate blocks for the insertion process for the purpose of increasing the imperceptibility of the proposed system. As for the extraction process, it is carried out in a way that requires the presence of the original image but rather follows the same embedding protocol to extract the embedded encrypted watermark. To raise the security level, a hybrid encryption method using the chaotic map and DNA coding has been applied for encrypting the watermark before embedding it. Experimental results demonstrate that the differences between the watermarked image and the original image are indistinguishable. The proposed method is effectively resisted common image processing attacks.